Three-dimensional ghost-fluid large-scale numerical investigation on air explosion. (28th September 2016) - Wang, Cheng; Ding, JianXu; Shu, Chi-Wang; Li, Tao
Highlights: Real ghost fluid method with level set method for air explosion. High order WENO finite difference scheme as the base algorithm. MPI-based parallel implementation. Study of overpressure for three-dimensional air explosion of both TNT and aluminized explosives. Abstract: Based on the double shockwave approximation procedure, a local Riemann solver for strongly nonlinear equations of state (EOS) such as the Jones–Wilkins–Lee (JWL) EOS is presented, which has suppressed successfully numerical oscillation caused by high-density ratio and high-pressure ratio across the interface between explosion products and air. The real ghost fluid method (RGFM) and the level set method have been used for converting multi-medium flows into pure flows and for implicitly tracking the interface, respectively. A fifth order finite difference weighted essentially non-oscillatory (WENO) scheme and a third order TVD Runge–Kutta method are utilized for the spatial discretization and the time advance, respectively. An enclosed-type MPI-based parallel methodology for the RGFM procedure on a uniform structured mesh is presented to realize the parallelization of three-dimensional (3D) air explosion. The overall process of 3D air explosion of both TNT and aluminized explosives has been successfully simulated. The overpressures at different locations of 3D air explosion for both explosives mentioned above are monitored and analyzed for revealing the influence of aluminum powder combustion on the overpressure of the explosion wave. Numerical results indicate that, due to aluminum powder afterburning, the attenuation of the explosion wave formed by aluminized explosives is slower than that caused by TNT.